OBESITAS SENTRAL PADA ORANG DEWASA: STUDI KOHOR PROSPEKTIF DI KOTA BOGOR - Sudikno Sudikno; Woro Riyadina; Ekowati Rahajeng (PERSATUAN AHLI GIZI INDONESIA, 2018)
Central obesity is one of the public health problems in developing countries. This study aims to analyze the dynamic risk factors for central obesity in adults. This study used secondary data